Hubungan antara status gangguan akibat kekurangan yodium (GAKY), status anemia dengan prestasi belajar anak sekolah dasar di Kabupaten Dairi Provinsi Sumatra Utara - Gema TD Sihite; Toto Sudargo; M G Adiyanti (Jurnal Gizi Klinik Indonesia, 2008)
Background: Disorders resulting from iodine deficiency and anemia will decrease learning achievement among elementary school children. Iodine deficiency has negative impacts on the growth of nervous cells that, in turn, influence their intelligence and learning ability. Also, the anemia condition will cause difficulties in logic and analogous thinking and decrease of concentration to study that have a negative impact in the form of declined learning achievement among the students.Objectives: To examine relationship between status of iodine deficiency disorder and learning achievement of elementary school children, examine relationship between status of anemia and learning achievement of elementary school children, and examine relationship between status of iodine deficiency disorder and status of anemia among the elementary children in Dairi District North Sumatra.Methods: This was an observational study using a cross-sectional design. The study population was all elementary school children in Dairi District and selected samples were 247 individuals. These samples were selected using multistage sampling design, where subjects were randomly selected. Data were processed with univariate analysis and statistical test was a bivariate using chi square test to find out relationship between status of iodine deficiency disorder and learning achievement among the elementary school children, relationship between status of anemia and learning achievement among elementary school children, and relationship between status of iodine deficiency disorder and status of anemia among the elementary school children. The entire data were processed with a computer.Results: The study indicated that there was relationship between status of iodine deficiency disorder and learning achievement among the elementary school children (p=0.000. There was also relationship between status of anemia and learning achievement among the elementary school children (p=0.001, OR=2.365), but there was no relationship between status of iodine deficiency disorder and status of anemia among the elementary school children (p=0.749).Conclusion: There were significant relationship between status of iodine deficiency disorder and status of anemia and learning achievement of elementary school children (p=0.001).